2010
DOI: 10.1007/s12080-010-0083-z
|View full text |Cite
|
Sign up to set email alerts
|

Can inverse density dependence at small spatial scales produce dynamic instability in animal populations?

Abstract: All else being equal, inversely density-dependent (IDD) mortality destabilizes population dynamics. However, stability has not been investigated for cases in which multiple types of density dependence act simultaneously.To determine whether IDD mortality can destabilize populations that are otherwise regulated by directly density-dependent (DDD) mortality, I used scale transition approximations to model populations with IDD mortality at smaller "aggregation" scales and DDD mortality at larger "landscape" scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…The zero-inflated component of the models accounts for the potential problems of heterogeneity in dispersion due to excessive zeros in the samples. In addition, the choice of the negative binomial distribution account for aggregation, that is common in soft sediment benthic organisms Gim enez and Yannicelli, 2000;Barbone and Basset, 2010;White, 2011;G omez and Defeo, 2012). Other solutions to these problems may consist in modelling presence/absence with logistic regression (e.g.…”
Section: Responses To Environmental Variablesmentioning
confidence: 99%
“…The zero-inflated component of the models accounts for the potential problems of heterogeneity in dispersion due to excessive zeros in the samples. In addition, the choice of the negative binomial distribution account for aggregation, that is common in soft sediment benthic organisms Gim enez and Yannicelli, 2000;Barbone and Basset, 2010;White, 2011;G omez and Defeo, 2012). Other solutions to these problems may consist in modelling presence/absence with logistic regression (e.g.…”
Section: Responses To Environmental Variablesmentioning
confidence: 99%
“…For example, Sandin and Pacala (2005) found predation on aggregating blue chromis (Chromis cyanea) to decrease as a function of group size and Stier et al (2013) found a similar pattern in shoaling bluntnose wrasse (Thalassoma amblycephalum). The degree to which inverse density dependence (Allee, 1941), leads to population instability depends on the strength of the Allee effect (Kramer et al, 2009) as well as co-occurring compensation (White, 2011). Kramer and Drake (2010) showed an increase in the probability of extinction as prey density declined from a predator-driven Allee effect in Daphnia magnus populations.…”
Section: Discussionmentioning
confidence: 99%
“…Redistribution of prey and predators across the landscape would probably occur in response to the local decline of prey density as prey seek to reduce predation risk through aggregation (Sutherland, 1983) and predators seek to reduce mutual interference (Kacelnik, Krebs, & Bernstein, 1992). White et al (2010) and White (2011) proposed that the patch defined by predators may exceed the size of the prey aggregation resulting in little effect on predator foraging behaviour and stabilisation of the effects of inverse density-dependent mortality. This phenomenon may explain the inverse density dependence observed as the predators' patch could have exceeded the size of our experimental system and prey were subjugated to concentrated predation pressure that would have otherwise been distributed over other local aggregations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the degree of bias involved in scaling up (or down) will depend on the degree of nonlinearity in the functional response and the magnitude of spatial variation in prey abundance. White (2011) used a coral reef fish example to illustrate how one can model variation in those two factors analytically and compare the results to field data to determine the degree to which large-scale dynamics are affected by the scale transition.…”
Section: Scale Transition Theory For Nonlinear Processes In Heterogenmentioning
confidence: 99%